The effects of public sector employment on the economy - Vincenzo Caponi (IZA World of Labor, 2017)
Public sector jobs are created because governments opt to provide goods and services produced directly by public employees. Governments, however, may also choose to regulate the size of the public sector in order to stabilize targeted national employment levels. However, economic research suggests that these effects are uncertain and critically depend on how public wages are determined. Rigid public sector wages lead to perverse effects on private employment, while flexible public wages lead to a stabilizing effect. Public employment also has important productivity and redistributive effects.
Keywords: E23; J45; 330; public sector employment; public sector wages; unemployment